Crossing paths crossing perspectives : urban studies in British Columbia and Quebec - Holden, Meg; Breux, Sandra (Etudes urbaines., 2023)
"This collection of urban studies research and interpretation crosses the country from Quebec to B.C., comparing trends and perspectives over the past decade and across and beyond disciplines. Core questions of research, policy and practice facing Montreal and Vancouver--those featuring housing and transportation, in particular--are featured in terms of new and innovative directions. Emerging questions--about urban indigeneity, food systems, climate action--are broached in challenging ways. The twenty authors whose original work is compiled here demonstrate the scope for continued, critical, comparative conversation across francophone and anglophone divides. The book offers a significant resource for understanding the intersecting field and practice of urban studies in Quebec and in B.C. and for spurring its further evolution."--